Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
On Generalized Choral Sequences

# On Generalized Choral Sequences

Ratings: (0)|Views: 14|Likes:
Presented at the Mathematical Society of the Philippines 2011 Annual Convention held at the University of Santo Tomas, Manila, Philippines on May 20-21, 2011
Presented at the Mathematical Society of the Philippines 2011 Annual Convention held at the University of Santo Tomas, Manila, Philippines on May 20-21, 2011

Published by: Joel Reyes Noche on May 18, 2011

### Availability:

Read on Scribd mobile: iPhone, iPad and Android.
See more
See less

05/18/2011

pdf

text

original

On Generalized Choral Sequences
Joel Reyes Noche
Department of Mathematics and Natural SciencesAteneo de Naga UniversityNaga City, Camarines Sur
Abstract
Generalized choral sequences are inﬁnite binary words (
c
n
)
n
0
deﬁned by
c
3
i
+
r
0
=
0
,
c
3
i
+
r
1
=
1
, and
c
3
i
+
r
c
=
c
i
(where the
r
’s are distinct ﬁxed elements of
{
0
,
1
,
2
}
)for all non-negative integers
i
. We present some of their properties. In particular, weshow how each is generated by a deterministic ﬁnite automaton with output and howeach is a ﬁxed point of a uniform morphism. We also look at their subword complexityand Lyndon factorizations.
1 Introduction
We use deﬁnitions and notation from Allouche and Shallit [1]. Denote by
N
the set of non-negative integers and by
Z
+
the set of positive integers. A
word
is a concatenation (asequence) of
letters
chosen from an
alphabet
(a non-empty set of letters). A
ﬁnite word
hasa ﬁnite
length
(the number of letters it contains) and is denoted by a lowercase italic letter.The length of a ﬁnite word
w
is denoted by
|
w
|
. The
empty word
, denoted by
, has a lengthof zero. A one-sided right-inﬁnite word (which we will simply call an
inﬁnite word
) is a mapfrom
N
to an alphabet and is denoted by a lowercase boldface letter. We call a word overthe alphabet
{
0,1
}
a
binary word
.Concatenation of words is denoted by the juxtaposition of their symbols. For example,if
w
=
0
and
x
=
01
, then
wx
=
001
,
xw
=
010
,
w
1
=
x
, and
wwxwx
=
w
(
wx
)
2
=
0
3
10
2
1
.We deﬁne
w
1
=
w
and
w
0
=
for any ﬁnite word
w
. If
x
is a ﬁnite non-empty word, then
x
ω
is the inﬁnite word
xxx
···
.A word
y
is a
subword
of
w
if there exist
x
and
z
such that
w
=
xyz
. If
x
=
, then
y
isa
preﬁx
of
w
. If
z
=
, then
y
is a
suﬃx
of
w
. If
x
=
and
z
=
, then
y
is a
proper preﬁx
of
w
. If
x
=
and
z
=
, then
y
is a
proper suﬃx
of
w
.We extend these deﬁnitions to inﬁnite words. An inﬁnite word
w
can be written as aninﬁnite sequence of ﬁnite subwords (
w
n
)
n
0
=
w
0
w
1
w
2
···
. A word
y
is a subword of
w
if there exist
x
and
z
such that
w
=
xy
z
. If
x
=
, then
y
is a preﬁx (and a proper preﬁx) of
w
. A word
z
is a subword (and a suﬃx) of
w
if there exists a
y
such that
w
=
y
z
. If
y
=
,then
z
is a proper suﬃx of
w
.The set of all ﬁnite words made up of letters chosen from an alphabet Σ is denoted byΣ
. Note that
Σ
. If
a
Σ and
w
Σ
, then
|
w
|
a
denotes the number of occurrencesof the letter
a
in the word
w
. The frequency of a letter
a
in an inﬁnite word
w
= (
w
n
)
n
0
1

(where the
w
’s are letters), denoted by Freq
w
(
a
), is lim
n
→∞
1
n
|
w
0
w
1
···
w
n
1
|
a
, if this limitexists.Let Σ and ∆ be alphabets. A
morphism
is a map
µ
from Σ
to
that obeys theidentity
µ
(
wx
) =
µ
(
w
)
µ
(
x
) for all words
w,x
Σ
. If Σ = ∆, then the application of amorphism can be iterated. For example, if
µ
is the morphism mapping
0
to
1
and
1
to
10
,then
µ
(
0
) =
1
,
µ
2
(
0
) =
µ
(
µ
(
0
)) =
µ
(
1
) =
10
, and so on. We deﬁne
µ
1
(
w
) =
µ
(
w
) and
µ
0
(
w
) =
w
for any word
w
.A morphism
µ
: Σ
is
k
-uniform
if there is a constant
k
such that
|
µ
(
a
)
|
=
k
forall
a
Σ. A
coding
is a 1-uniform morphism.A
ﬁxed point
of a morphism
µ
: Σ
Σ
is a ﬁnite word
w
(or inﬁnite word
w
) suchthat
µ
(
w
) =
w
(or
µ
(
w
) =
w
). If there exists a letter
a
Σ such that
µ
(
a
) =
ax
and
x
is aword composed of letters
x
i
Σ such that
µ
m
(
x
i
)
=
for any
m
Z
+
, then the morphism
µ
is
prolongable
on the letter
a
. If so, then lim
m
→∞
µ
m
(
a
) (denoted by
µ
ω
(
a
)) is the ﬁxedpoint of
µ
iterated on
a
, where the length of the iterates from the letter
a
tends to inﬁnity.Let
w
denote the
complement
of the ﬁnite binary word
w
(and
w
denote the complementof the inﬁnite binary word
w
) where the overbar represents the morphism mapping
0
1
and
1
0
. For example, if
w
=
001
, then
w
=
110
.Given a ﬁnite word
w
=
a
0
a
1
···
a
n
, where the
a
’s are letters, its
reversal
, denoted by
w
R
, is
a
n
···
a
1
a
0
.
Deﬁnition 1.
A
generalized choral sequence
is an inﬁnite binary word
c
(
r
0
,r
1
,r
c
,z
) =(
c
n
)
n
0
deﬁned by
c
3
i
+
r
0
=
0
,
c
3
i
+
r
1
=
1
,
c
3
i
+
r
c
=
c
i
, and
c
0
=
z
(where the
r
’s are distinct  ﬁxed elements of
{
0
,
1
,
2
}
and
z
=
0
if
r
0
= 0
,
z
=
1
if
r
1
= 0
, and
z
could either be
0
or
1
if
r
c
= 0
) for all
i
N
.
There are eight distinct choral sequences: (Spaces have been inserted to improve read-ability.)
c
(0
,
2
,
1
,
0
) =
001001011 001001011 001011011
···
c
(1
,
2
,
0
,
0
) =
001001101 001001101 101001101
···
c
(0
,
1
,
2
,
0
) =
010011010 010011011 010011010
···
c
(2
,
1
,
0
,
0
) =
010110010 110110010 010110010
···
c
(1
,
2
,
0
,
1
) =
101001101 001001101 101001101
···
c
(1
,
0
,
2
,
1
) =
101100101 101100100 101100101
···
c
(2
,
1
,
0
,
1
) =
110110010 110110010 010110010
···
c
(2
,
0
,
1
,
1
) =
110110100 110110100 110100100
···
Sequence
c
(0
,
2
,
1
,
0
) is Stewart’s choral sequence. (Stewart [11] presented the sequence(
c
n
)
n
1
and not (
c
n
)
n
0
.) Sequence
c
(0
,
1
,
2
,
0
) is from Berstel and Karhum¨aki [2].
Deﬁnition 2.
A generalized choral sequence
c
(
r
0
,r
1
,r
c
,z
)
is called a
type-012 sequence
if
(
r
0
,r
1
,r
c
)
is a circular permutation of
(0
,
1
,
2)
. Otherwise (i
(
r
0
,r
1
,r
c
)
is a circular permutation of
(2
,
1
,
0)
), it is called a
type-210 sequence
.
2 Some Properties
A previous work [8] presented a characteristic function for generalized choral sequences aswell as proofs of the following two theorems.
Theorem 1.
A generalized choral sequence is
cube-free
, that is, it does not contain any subword of the form
xxx
, where
x
is a non-empty ﬁnite subword.
2

Theorem 2.
Given two generalized choral sequences, if they are both type-012 (or if they are both type-210) then any ﬁnite subword of one is a subword of the other. Otherwise, any  ﬁnite subword of one is the complement of a subword of the other.
The following theorem is related to the previous theorem and their proofs are similar.
Theorem 3.
Given a type-012 sequence and a type-210 sequence, any ﬁnite subword of oneis the reversal of a subword of the other.Proof.
Let
v
= (
v
n
)
n
0
be the given type-012 sequence and
w
= (
w
n
)
n
0
be the giventype-210 sequence. We will show that any ﬁnite subword of
v
is the reversal of a subwordof
w
. (The proof that any ﬁnite subword of
w
is the reversal of a subword of
v
is similar.)Because any generalized choral sequence has all the subwords
001
,
010
,
011
,
100
,
101
,and
110
[8], any length-3 subword of
v
is the reversal of a subword of
w
. That is, for agiven
j
N
, there exists a
k
N
such that
v
j
v
j
+1
v
j
+2
=
w
k
+2
w
k
+1
w
k
.By Deﬁnition 2, there exists a subword
v
3
j
+
r
c
v
3
j
+
r
c
+1
v
3
j
+
r
c
+2
v
3
j
+
r
c
+3
v
3
j
+
r
c
+4
v
3
j
+
r
c
+5
v
3
j
+
r
c
+6
=
v
j
01
v
j
+1
01
v
j
+2
and a subword
w
3
k
+
r
c
w
3
k
+
r
c
+1
w
3
k
+
r
c
+2
w
3
k
+
r
c
+3
w
3
k
+
r
c
+4
w
3
k
+
r
c
+5
w
3
k
+
r
c
+6
=
w
k
10
w
k
+1
10
w
k
+2
such that
v
j
01
v
j
+1
01
v
j
+2
=
w
k
+2
01
w
k
+1
01
w
k
.Any length-5 subword of
v
is a subword of a length-7 subword of the form
v
3
j
+
r
c
v
3
j
+
r
c
+1
v
3
j
+
r
c
+2
v
3
j
+
r
c
+3
v
3
j
+
r
c
+4
v
3
j
+
r
c
+5
v
3
j
+
r
c
+6
. Thus, any length-5 subword of
v
is the reversalof a subword of
w
. (This is also true for subwords of length less than 5.)Extending this reasoning to arbitrarily long ﬁnite subwords of similar form yields theresult that any ﬁnite subword of
v
is the reversal of a subword of
w
.
Remark 1.
For any generalized choral sequence
c
,
Freq
c
(
0
) =
12
and
Freq
c
(
1
) =
12
.
We ﬁrst show that Freq
c
(
0
) =
12
. Let
c
= (
c
n
)
n
0
. Consider the subword
c
0
c
1
···
c
n
1
with length
n
. As
n
, around
13
of the letters of
c
0
c
1
···
c
n
1
will be due to the subwords
c
3
i
+
r
0
, around
13
will be due to
c
3
i
+
r
1
, and around
13
will be due to
c
3
i
+
r
c
, for
i
N
suchthat 3
i
+
r < n
.Since
c
3
i
+
r
0
=
0
, the number of occurrences of
0
due to the subwords
c
3
i
+
r
0
approaches
n
3
as
n
. Since
c
3
i
+
r
1
=
1
, the number of occurrences of
0
due to the subwords
c
3
i
+
r
0
and
c
3
i
+
r
1
still approaches
n
3
as
n
.Now consider the subwords
c
3
i
+
r
c
. Since
c
3
i
+
r
c
=
c
i
, one third of the subwords
c
3
i
+
r
c
will be
0
, and one third will be
1
. Of the remaining subwords, one third will be
0
, one thirdwill be
1
and so on.Thus, the number of occurrences of
0
in the subword
c
0
c
1
···
c
n
1
as
n
→ ∞
approaches
n
3
1 +
13
1 +
13
(1 +
···
)

=
n
3
+
n
3
2
+
n
3
3
+
···
and Freq
c
(
0
) = lim
n
→∞
1
n
n
3
+
n
3
2
+
n
3
3
+
···
=
i
=113
i
=
1 +
i
=1
13
i
1
=
1 +
11
13
=
12
.Using similar reasoning, we can show that Freq
c
(
1
) =
12
.
Proposition 1. c
(1
,
2
,
0
,z
) =
z
c
(0
,
1
,
2
,
0
)
and
c
(2
,
1
,
0
,z
) =
z
c
(1
,
0
,
2
,
1
)
Proof.
We ﬁrst show that
c
(1
,
2
,
0
,z
) =
z
c
(0
,
1
,
2
,
0
). Let (
a
n
)
n
0
=
c
(1
,
2
,
0
,z
), (
b
n
)
n
0
=
c
(0
,
1
,
2
,
0
), and (
c
n
)
n
0
=
z
c
(0
,
1
,
2
,
0
). Thus,
a
3
i
+1
=
0
,
a
3
i
+2
=
1
,
a
3
i
=
a
i
,
b
3
i
=
0
,
b
3
i
+1
=
1
, and
b
3
i
+2
=
b
i
for all
i
N
. Also,
c
i
+1
=
b
i
for all
i
N
so
c
3
i
+1
=
b
3
i
=
0
,
c
3
i
+2
=
b
3
i
+1
=
1
, and
c
3
i
+3
=
b
3
i
+2
=
b
i
=
c
i
+1
for all
i
N
. Since
c
3(
i
+1)
=
c
i
+1
for
i
N
and
c
3
·
0
=
c
0
,
c
3
i
=
c
i
for all
i
N
. Also,
a
3
i
+1
=
0
=
c
3
i
+1
and
a
3
i
+2
=
1
=
c
3
i
+2
for all
i
N
.3

## Activity (1)

You've already reviewed this. Edit your review.